The interface between the written and the oral - Goody, Jack (Cambridge Cambridge University Press, 1987)
Whilst the fundamental significance of the spoken language for human interaction is widely acknowledged, that of writing is less well known, and in this wide-ranging series of essays Jack Goody examines in depth the complex and often confused relationship between oral and literate modes of communication. He considers the interface between the written and the oral in three cultures or societies with and without writing, and that within the linguistic life of an individual. Specific analyses of the sequence of historical change within writing systems, the historic impact of writing upon Eurasian cultures, and the interaction between distinct oral and literate cultures in West Africa, precede an extensive concluding examination of contemporary issues in the investigation, whether sociological or psychological, of literacy. A substantial corpus of anthropological, historical and linguistic evidence is produced in support of Goody's findings, which form a natural complement to his own recently published study of The Logic of Writing and the Organization of Society.